2012
DOI: 10.1016/j.chom.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Host Cell Autophagy Activated by Antibiotics Is Required for Their Effective Antimycobacterial Drug Action

Abstract: The current standard of treatment against tuberculosis consists of a cocktail of first-line drugs, including isoniazid and pyrazinamide. Although these drugs are known to be bactericidal, contribution of host cell responses in the context of antimycobacterial chemotherapy, if any, remains unknown. We demonstrate that isoniazid and pyrazinamide promote autophagy activation and phagosomal maturation in Mycobacterium tuberculosis (Mtb)-infected host cells. Treatment of Mtb-infected macrophages with isoniazid or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
245
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(263 citation statements)
references
References 40 publications
(52 reference statements)
9
245
0
9
Order By: Relevance
“…In fact, it has been established that prolonged use of autophagy inhibitors, such as azitromycin, inhibits intracellular killing of mycobacteria and predisposes cystic fibrosis patients to mycobacterial disease (Renna et al, 2011). Furthermore, autophagy was shown to be the determinant in the intracellular killing effect of the first-line TB drugs, isoniazid and pyrazinamide, through a mechanism based on the release of ROS (Kim et al, 2012a). Therefore, autophagy inducers can and are being explored as potential new TB therapies.…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…In fact, it has been established that prolonged use of autophagy inhibitors, such as azitromycin, inhibits intracellular killing of mycobacteria and predisposes cystic fibrosis patients to mycobacterial disease (Renna et al, 2011). Furthermore, autophagy was shown to be the determinant in the intracellular killing effect of the first-line TB drugs, isoniazid and pyrazinamide, through a mechanism based on the release of ROS (Kim et al, 2012a). Therefore, autophagy inducers can and are being explored as potential new TB therapies.…”
Section: Arg677trp (C2029t)mentioning
confidence: 99%
“…85 Thus, a strong association between defective autophagy and impaired properties counteracting bacterial infections has been reported by numerous studies. 73,[86][87][88][89] However, a recent study has revealed a protective role of Atg16l1 deficiency against intestinal disease induced by the bacterial pathogen model, Citrobacter rodentium. This immunosuppressive role of ATG16L1 deficiency is dependent on the presence of NOD2 90 and adds to the complexity of the role of ATG16L1 in bacterial clearance.…”
Section: Atg16l1-dependent Signaling In Crohn Diseasementioning
confidence: 99%
“…9 Recent studies have demonstrated a role for AMPK signaling in the autophagy process, a catabolic pathway of cytoplasmic materials and organelles, whereas MTOR (mechanistic target of rapamycin) is reported to have converse effects. [10][11][12] The complex protein network comprising AMPK, MTOR, and ULK1/2 (unc-51 like autophagy activating kinase 1/2) is considered to be important for coordinating autophagic responses during a variety of cell stress conditions. 12 In addition to autophagy activation, AMPK signaling is critically involved in mitochondrial biogenesis and activation.…”
Section: Introductionmentioning
confidence: 99%